The pregnane X receptor down‐regulates organic cation transporter 1 (SLC22A1) in human hepatocytes by competing for ("squelching") SRC‐1 coactivator. (8th April 2016) - Hyrsova, Lucie; Smutny, Tomas; Carazo, Alejandro; Moravcik, Stefan; Mandikova, Jana; Trejtnar, Frantisek; Gerbal‐Chaloin, Sabine; Pavek, Petr
Abstract : Background and Purpose: The organic cation transporter 1 (OCT1) transports cationic drugs into hepatocytes. The high hepatic expression of OCT1 is controlled by the HNF4α and USF transcription factors. Pregnane X receptor (PXR) mediates induction of the principal xenobiotic metabolizing enzymes and transporters in the liver. Here, we have assessed the down‐regulation of OCT1 expression by PXR activation. Experimental Approach: We used primary human hepatocytes and related cell lines to measure OCT1 expression and activity, by assaying MPP + accumulation. Western blotting, qRT‐PCR, the OCT1 promoter gene reporter constructs and chromatin immunoprecipitation assays were also used. Key Results: OCT1 mRNA in human hepatocytes was down‐regulated along with reduced [ 3 H]MPP + accumulation in differentiated HepaRG cells after treatment with rifampicin. Rifampicin and hyperforin as well as the constitutively active PXR mutant T248D suppressed activity of the 1.8 kb OCT1 promoter construct in gene reporter assays. Silencing of both PXR and HNF4α in HepaRG cells blocked the PXR ligand‐mediated down‐regulation of OCT1 expression. The mutation of HNF4α and USF1 (E‐box) responsive elements reversed the PXR‐mediated inhibition in gene reporter assays. Chromatin immunoprecipitation assays indicated that PXR activation sequestrates the SRC‐1 coactivator from the HNF4α response element and E‐box of the OCT1 promoter. Consistent with these findings, exogenous overexpression of the SRC‐1, but not the PGC1α coactivator, relieved the PXR‐mediated repression of OCT1 transactivation. Conclusions and Implications: PXR ligands reduced the HNF4α‐mediated and USF‐mediated transactivation of OCT1 gene expression by competing for SRC‐1 and decreased delivery of a model OCT1 substrate into hepatocytes.